Divorciarse en Cataluña a finales del Antiguo Régimen: ¿rechazo o solidaridad social? - Marie Costa (Nuevo mundo - Mundos Nuevos, 2007)
In this work we aim at a deep understanding of the marriage conflicts and divorce in Catalonia during a key period corresponding to the end of the Old Regime when the liberal ideology arises (1775-1833). We focus on different aspects related to the marriage conflicts such as gender relations, canonical rigths, solidarity networks, etc. We draw attention to the terminological duality of divorce (formal and informal) as well as to the implications and consequences derived from it when legalized by the ecclesiastical tribunal of Barcelona and Girona dioceses (women kidnap in a honest home, division of properties, allowances, etc.). Additionaly, we explain to what extent the studied society takes part in the conflicts.